2018
DOI: 10.1037/lhb0000287
|View full text |Cite
|
Sign up to set email alerts
|

The presumption of guilt in suspect interrogations: Apprehension as a trigger of confirmation bias and debiasing techniques.

Abstract: This research tests whether a police officer's decision to apprehend a suspect triggers confirmation bias during an interrogation. The study also tests two strategies to reduce confirmation bias: (1) decoupling decision to apprehend from interrogation and (2) reducing cognitive load for the interrogating police officer. In Experiment 1, Swedish police officers ( = 60) were faced with 12 scenarios in which they either had to decide for themselves whether to apprehend a suspect or were informed about the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 61 publications
1
14
0
1
Order By: Relevance
“…Thus, even if lineup administrators are blind to which lineup member is the suspect, the interaction between the administrator and the witness may still prove problematic. For example, it would not be surprising if lineup administrators are certain of suspects’ guilt, irrespective of their actual guilt, because research on interrogations and false confessions makes clear that interrogators are guilt presumptive (Lidén et al, 2018; Meissner & Kassin, 2002). What if these guilt presumptive administrators are constrained from repeating an identification with a witness?…”
Section: Future Directions For Studying Eyewitness Identification In ...mentioning
confidence: 99%
“…Thus, even if lineup administrators are blind to which lineup member is the suspect, the interaction between the administrator and the witness may still prove problematic. For example, it would not be surprising if lineup administrators are certain of suspects’ guilt, irrespective of their actual guilt, because research on interrogations and false confessions makes clear that interrogators are guilt presumptive (Lidén et al, 2018; Meissner & Kassin, 2002). What if these guilt presumptive administrators are constrained from repeating an identification with a witness?…”
Section: Future Directions For Studying Eyewitness Identification In ...mentioning
confidence: 99%
“…Some criminal justice professionals and scholars assume that experience and training which judges, lawyers, and police officers receive or training which police trainees or law students receive equips them to make more accurate decisions in cases than jurors or community members (e.g., Kahan, 2015 cf. Lidén, Gräns, & Juslin, 2018). Judges often write about how they believe jurors are easily influenced by bias and their emotions (e.g., Edwards, 1984; Hans & Vidmar, 1986) and prosecutors often raise jurors’ beliefs in victim stereotypes as an impediment to prosecution in rape cases but not necessarily an issue in their own decision-making (Bluett-Boyd & Fileborn, 2014; Temkin, 2000; Temkin & Krahé, 2008).…”
Section: Sample Typementioning
confidence: 99%
“…This implies that humans reason in a one-sided way in order to convince others that they are right (Mercier, 2016;Mercier & Sperber, 2011) and want to defend their ideas and behaviors in order to maintain control and self-esteem (Pyszczynski & Greenberg, 1987). In line with this, research has found that confirmation bias seems to be stronger in relation to self-generated hypotheses than others' hypotheses, in both the legal context (Lidén et al, 2018) and other contexts (Dunbar & Klahr, 1989;Haverkamp, 1993;Klahr, Dunbar, & Fay, 1990;Schunn & Klahr, 1992, 1993. In this research, the notion of confirmation bias as a self-enhancement bias is tested by changing decision maker between the arrest and prosecution to see whether this is functional as a debiasing technique.…”
Section: Introductionmentioning
confidence: 90%
“…A common situation in the Swedish setting is that the police has decided to apprehend a suspect (Lidén, Gräns, & Juslin, 2018) and the prosecutor then has to decide whether the deprivation of liberty shall be maintained, that is, whether the suspect shall be arrested. In this assessment, they have to evaluate the evidence available to decide whether the evidentiary requirements for an arrest are fulfilled.…”
Section: Introductionmentioning
confidence: 99%